AN INTEREST-FREE ECONOMY: ADDRESSING THE CHALLENGES OF THE TIMES AMID THE RISE OF ONLINE LENDING AND HIGH INTEREST RATES - Nur Rahmad Iqbal; Mahatir Muhammad Sidebang; Kemal Muhammad Afif (Universitas Efarina, 2023)
The widespread emergence of high-interest online lending (commonly known as pinjol in Indonesia) has raised significant economic, social, and spiritual concerns within society. Conventional financial systems, which are fundamentally based on interest (riba), are increasingly seen as contributors to economic injustice, social disparity, and structural exploitation, particularly among vulnerable groups. This paper examines the Islamic economic system as a comprehensive and value-based alternative to build a riba-free economy that is just, inclusive, and sustainable. Using a qualitative-descriptive approach, the study explores core Islamic principles such as ‘adl (justice), amanah (trust), maslahah (public welfare), and the prohibition of riba, positioning them as essential foundations for responding to the contemporary financial crisis driven by consumerism and digital debt traps. Furthermore, the research analyzes the mechanisms of pinjol operations, the socio- economic impacts on low-income communities, and proposes practical strategies to strengthen Sharia-compliant financial systems through technological innovation and financial literacy campaigns. The findings suggest that the implementation of a riba-free economic model is not only feasible but urgently necessary in today’s digital era. By reorienting financial behavior toward ethical and spiritually conscious values, the Islamic economic system offers a transformative framework capable of addressing the root causes of financial injustice and promoting holistic well-being